Peran Orang Tua dalam Proses Pembelajaran Daring - Zuraidah Adlina; Syahlan Syahlan; Asnawati Matondang (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The learning process is a social interaction that is carried out by students and teaching staff in sharing information and knowledge. During the process, learning activities are more likely to be carried out online, either using social media, teleconferencing devices, or other applications that can be used to convey messages/information, record material, or face-to-face virtual. For this reason, the learning process does not only need to be supervised by teaching staff, but also the role of parents in the online learning process. This research is a qualitative research with a descriptive approach that will provide an overview of the role of parents in the online learning process. The role of parents who become aspects of observation include: the facilities provided and the motivation provided. The sample in this study were all students of the Faculty of Teacher Training and Education, Islamic University of North Sumatra. The existing sample was chosen randomly with a total sample of 32 students. Analysis of the data used is using interpretation analysis based on the opinions and perceptions of students in terms of parental support for the online learning process. Based on the information collected from students regarding the role of parents, it is concluded that providing facilities to support the online learning process and providing motivation is a form of parental participation in the success of online learning.